2020
DOI: 10.14710/jil.18.2.354-366
|View full text |Cite
|
Sign up to set email alerts
|

Beban Pencemaran BOD dan Karakteristik Oksigen Terlarut di Sungai Brantas Kota Malang

Abstract: Sungai Brantas memiliki fungsi penting bagi provinsi Jawa Timur, 60% pengairan lahan produksi beras berasal dari aliran sungai ini. Observasi lapang menunjukkan bahwa terdapat banyak bangunan rumah mendekati area sungai bahkan sampai melewati batas, hal ini juga terjadi khususnya di area Kota Malang. Rekaman laporan indeks kualitas air di Jawa Timur Tahun 2015 tercatat berada di angka 52.51 dengan status sangat rendah dan terus menurun dengan angka 50.75 pada tahun 2016 dengan status yang waspada. Berdasarkan … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
10

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 0 publications
1
7
0
10
Order By: Relevance
“…Changes in the increase in TSS content that affect surface runoff dissolving into water bodies are suspected of changes in requirements and land use in the Klampok Sub-watershed area. This result is similar to that of Lusiana et al (2020) that the TSS content in the Brantas River, Malang City, was below the quality standard, where the TSS value was influenced by the amount of sediment in the water body carried by surface runoff and open land around the water body. The high content of TSS also occurs in the Sani River, Pati Regency, Central Java at 19 to 108 mg l -1 due to the input of sediment and solids in the river body (Mailisa et al, 2021).…”
Section: Water Quality In the Klampok Sub-watershedsupporting
confidence: 86%
See 1 more Smart Citation
“…Changes in the increase in TSS content that affect surface runoff dissolving into water bodies are suspected of changes in requirements and land use in the Klampok Sub-watershed area. This result is similar to that of Lusiana et al (2020) that the TSS content in the Brantas River, Malang City, was below the quality standard, where the TSS value was influenced by the amount of sediment in the water body carried by surface runoff and open land around the water body. The high content of TSS also occurs in the Sani River, Pati Regency, Central Java at 19 to 108 mg l -1 due to the input of sediment and solids in the river body (Mailisa et al, 2021).…”
Section: Water Quality In the Klampok Sub-watershedsupporting
confidence: 86%
“…The BOD content decreased at sampling point 3 since sampling location point 3 was the accumulation of pollution points from points 1 and 2 and had a longer distance than the previous sampling point. The pollutant had been reduced by increasing the distance of the river flow so that the number of pollutants received was smaller at the receiving location of the pollution accumulation than at the previous sampling locations (Lusiana et al, 2020).…”
Section: Water Quality In the Klampok Sub-watershedmentioning
confidence: 99%
“…Sungai Brantas merupakan sungai terbesar kedua di Pulau Jawa dan terpanjang di Provinsi Jawa Timur. Sungai Brantas memiliki panjang ± 320 km dan luasnya ± 14.103 km 2 (Lusiana et al 2020). Sungai Brantas merupakan habitat bagi keberadaan berbagai jenis ikan.…”
Section: Pendahuluanunclassified
“…The observation results of one segment in Metro River showed that COD levels exceeded the water quality standards required by the government. Meanwhile, the Metro River water flowing along the areas of Pisang Candi, Karang Besuki, Bandulan, and Sitirejo was moderately polluted water with an ASPT value of 4 -6.2 [7].…”
Section: Introductionmentioning
confidence: 99%